Distribuição espacial de atributos químicos do solo em área de pastagem e floresta - Aquino, Renato Eleoterio De [UNESP]; Marques Júnior, José [UNESP]; Campos, Milton Cesar Costa; Oliveira, Ivanildo Amorim De [UNESP]; Siqueira, Diego Silva [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2014)
The knowledge on spatial distribution of soil properties by means of geostatistics is important as an indicator for a better soil use and management. This study aimed at evaluating the spatial distribution of soil chemical properties, in a forest and pasture area in Manicoré, Amazonas State, Brazil. Grids with 70.00 m x 70.00 m, with regular spacing of 10.00 m x 10.00 m, totaling 64 points, were established, and then soil samples were collected at the depths of 0.0-0.20 m and 0.40-0.60 m and had their chemical properties determined. Data were analyzed by using descriptive statistics and geostatistics, and the sampling density analysis was based on the coefficient of variation and semivariograms range. The mean and median values were adjusted to the closest values, indicating normal distribution, while the spherical, exponential and gaussian models were adjusted to the soil chemical properties. It was concluded that the geostatistics provided adequate information for understanding the spatial distribution. The forest area showed a higher spatial continuity and the pasture area a lower sampling density. The chemical properties showed differences in the spatial variability, while the range represented better the estimates for sampling density and spacing, in the forest and pasture area.

O conhecimento da distribuição espacial de atributos do solo, por meio da geoestatística, é importante como indicador para um melhor uso e manejo do solo. Este estudo objetivou avaliar a distribuição espacial de atributos químicos do solo, em área de pastagem e floresta, na região de Manicoré (AM). Foram estabelecidas malhas de 70,00 m x 70,00 m, com espaçamento regular de 10,00 m x 10,00 m, totalizando 64 pontos, e, em seguida, coletadas amostras de solo, às profundidades de 0,0-0,20 m e 0,40-0,60 m, sendo determinados os seus atributos químicos. Os dados foram analisados utilizando-se técnicas de estatística descritiva e geoestatística, e a densidade amostral determinada com base no coeficiente de variação e no alcance dos semivariogramas. Os valores da média e mediana se ajustaram aos valores próximos, indicando distribuição normal, enquanto os modelos esférico, exponencial e gaussiano se ajustaram aos atributos químicos do solo. Concluiu-se que a geoestatística forneceu informações adequadas para a compreensão da distribuição espacial. A área com floresta apresentou maior continuidade espacial e a área com pastagem menor densidade amostral. Os atributos químicos evidenciaram diferenças na variabilidade espacial, enquanto o alcance representou melhor as estimativas para a densidade amostral e espaçamento, na área de floresta e pastagem.
Spatial distribution of soil chemical properties in pasture and forest area
Keywords: Spatial variability; Geostatistics; sampling density; Variabilidade espacial; Geoestatística; densidade amostral